2015
DOI: 10.1007/s10554-015-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Mitral regurgitation quantification by cardiovascular magnetic resonance: a comparison of indirect quantification methods

Abstract: Quantification of mitral regurgitation (MR) using cardiovascular magnetic resonance can be achieved by three indirect methods. The aims of the study were to determine their agreement, observer variability and effect on grading MR severity. The study comprised 16 healthy volunteers and 36 MR patients. Quantification was performed using the 'standard' [left ventricular stroke volume (LVSV)-aortic forward flow (AoFF)], 'volumetric' [LVSV-right ventricular stroke volume (RVSV)] and 'flow' method [mitral inflow (Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Several CMR approaches have been used including the comparison of the LVSV with the RVSV [ 13 ], LVSV with the Ao forward by phase-contrast cine imaging [ 15 , 17 ], trans-mitral forward flow with Ao forward [ 12 , 23 ], or by direct measurement of the regurgitant orifice area [ 24 ]. However, these methods were not specifically validated for MVP patients and they seem not to be interchangeable, as they can differ in quantitative measures of regurgitation as well as with respect to inter-observer reproducibilities [ 25 , 26 ]. In case of MVP, the present study suggests that MR quantification has to be adapted to the mechanism of MR to minimize the risk of misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Several CMR approaches have been used including the comparison of the LVSV with the RVSV [ 13 ], LVSV with the Ao forward by phase-contrast cine imaging [ 15 , 17 ], trans-mitral forward flow with Ao forward [ 12 , 23 ], or by direct measurement of the regurgitant orifice area [ 24 ]. However, these methods were not specifically validated for MVP patients and they seem not to be interchangeable, as they can differ in quantitative measures of regurgitation as well as with respect to inter-observer reproducibilities [ 25 , 26 ]. In case of MVP, the present study suggests that MR quantification has to be adapted to the mechanism of MR to minimize the risk of misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…While this convention allows for reproducibility, misidentification of portions of the left atrium as ventricle leads to overestimation in the MRVol. Using this technique, half of healthy volunteers (without any visible MR) had a calculated MRVol >10 mL/beat 3. To minimise these limitations, we favour the standardisation of techniques within a centre with reporting of the technique used in order to enhance centre-to-centre comparisons.…”
Section: Methods Of Mr Quantificationmentioning
confidence: 99%
“…In a prospective study of 26 subjects with MR in our centre, Cawley et al 4 showed that the LVsv-Ao flow technique had better intraobserver and interobserver reproducibility when compared with the LVsv-RVsv technique. Polte et al 3 compared MRVol calculations using LVsv-Ao, LVsv-RVsv and mitral annular flow methods. The LVsv-Ao resulted in the highest MRVol of the three techniques, but overestimated MR in healthy volunteers in whom no MR was visibly present by 15–20 mL/beat.…”
Section: Reproducibility Of Cmr Techniquesmentioning
confidence: 99%
“…A common method calculates MR based on differential forward stroke volume between the mitral valve and aortic valve, which can each be calculated via PC-CMR sampling at the respective valve orifices (23). One pitfall of this approach stems from translational valve motion, which can produce under-sampling of flow and produce errors in MR quantification (19). A variant of this approach employs PC-CMR to sample flow through the aortic valve (a region with lesser translational motion than the mitral valve), and cine-CMR to measure LV stroke volume (∆ end-diastole − end-systole); differential stroke volume corresponds to the amount of MR (Figure 1) (24).…”
Section: Quantification Of Mrmentioning
confidence: 99%
“…A variety of CMR pulse sequences can be used for MR assessment ( Table 1). Phase velocity encoded CMR can quantify MR severity based on both direct measures of regurgitant flow through the mitral valve as well as indirect measures of differential stroke volumes (19). Cine-CMR can identify mitral valve alterations (e.g., prolapse, rheumatic disease) as well as secondary changes in the mitral apparatus (e.g., papillary muscle displacement) that pre-dispose to MR (20).…”
mentioning
confidence: 99%